Resistance to mercury and to cadmium in chromosomally resistant Staphylococcus aureus. - Witte, W (1986)
Apparently chromosomally located mercury resistance determinants in five methicillin-resistant Staphylococcus aureus strains of different geographical origin were structurally homologous to plasmid-located mercury resistance determinants in S. aureus. These were all located on a 6.3-kilobase (kb) Bg/II fragment, as evident from Southern hybridization experiments with the 6.3-kb Bg/II fragment of plasmid pI258 as the probe. These methicillin-resistant S. aureus strains exhibited similar phage susceptibility patterns and biochemical reactions. They differed, however, in the DNA location of the mercury resistance determinants, as evidenced by neighboring cleavage sites for restriction endonucleases EcoRI, HindIII, and PstI. In an environmental (nonhospital) strain in which mercury resistance was also apparently chromosomally conferred, these determinants were also homologous to pI258 DNA, but they were located on a 6.6-kb Bg/II fragment. Cadmium resistance determinants in the five methicillin-resistant S. aureus strains and the environmental S. aureus strain were not similar to the known plasmid-located determinants cadA and cadB. Cd2+ resistance was based on an efflux mechanism for Cd2+. However, no parallel resistance to zinc was conferred. The 3.2-kb XbaI-Bg/II fragment obtained from plasmid pI258 and used as a cadA-specific probe did not hybridize to total DNA digests of the strains with apparently chromosomally determined cadmium resistance.